Iron and Zinc in the Embryo and Endosperm of Rice (Oryza sativa L.) Seeds in Contrasting 2′-Deoxymugineic Acid/Nicotianamine Scenarios - Díaz-Benito, Pablo; Banakar, Raviraj; Rodríguez-Menéndez, Sara; Capell, Teresa; Pereiro, Rosario; Christou, Paul; Abadía, Javier; Fernández, Beatriz; Álvarez-Fernández, Ana (Frontiers in Plant Science, 2018)
Iron and Zn deficiencies are worldwide nutritional disorders that can be alleviated by increasing the metal concentration of rice (Oryza sativa L.) grains via bio-fortification approaches. The overproduction of the metal chelator nicotianamine (NA) is among the most effective ones, but it is still unclear whether this is due to the enrichment in NA itself and/or the concomitant enrichment in the NA derivative 2'-deoxymugineic acid (DMA). The endosperm is the most commonly consumed portion of the rice grain and mediates the transfer of nutrients from vegetative tissues to the metal rich embryo. The impact of contrasting levels of DMA and NA on the metal distribution in the embryo and endosperm of rice seeds has been assessed using wild-type rice and six different transgenic lines overexpressing nicotianamine synthase (OsNAS1) and/or barley nicotianamine amino transferase (HvNAATb). These transgenic lines outlined three different DMA/NA scenarios: i) in a first scenario, an enhanced NA level (via over expression of OsNAS1) would not be fully depleted because of a limited capacity to use NA for DMA synthesis (lack of -or low- expression of HvNAATb), and results in consistent enrichments in NA, DMA, Fe and Zn in the endosperm and NA, DMA and Fe in the embryo; ii) in a second scenario, an enhanced NA level (via overexpression of OsNAS1) would be depleted by an enhanced capacity to use NA for DMA synthesis (via expression of HvNAATb), and results in enrichments only for DMA and Fe, both in the endosperm and embryo, and iii) in a third scenario, the lack of sufficient NA replenishment would limit DMA synthesis, in spite of the enhanced capacity to use NA for this purpose (via expression of HvNAATb), and results in decreases in NA, variable changes in DMA and moderate decreases in Fe in the embryo and endosperm. Also, quantitative LA-ICP-MS metal map images of the embryo structures show that the first and second scenarios altered local distributions of Fe, and to a lesser extent of Zn. The roles of DMA/NA levels in the transport of Fe and Zn within the embryo are thoroughly discussed.